The Louisiana Mental and Behavioral Health Capacity Project Trauma-Informed Integrated Care Model and Improved Posttraumatic Stress Outcomes. (November 2017) - Osofsky, Howard J.; Osofsky, Joy D.; Hansel, Tonya Cross; Flynn, Trevor
Abstract : Objective: The Mental and Behavioral Health Capacity Project in Louisiana has been addressing health disparities by increasing accessibility and availability through integrating services into primary care clinics. Integrated health is becoming the standard of care, providing an opportunity to address the trauma-specific needs of communities, and allowing for informed and less stigmatized services. The purpose of this study is to test the efficacy of the Mental and Behavioral Health Capacity Project in Louisiana model in the primary care settings to reduce posttraumatic stress symptoms and physical health complaints. Design: A pre-experimental time series design was used on the basis of participants self-reporting at least 1 trauma at intake and follow-up collected at 1-, 3-, and 6-month intervals. The hypotheses were that posttraumatic stress and physical health complaints would significantly decrease over the course of treatment. Setting: This study was part of a larger study to evaluate the effectiveness of the Mental and Behavioral Health Capacity Project in Louisiana–integrated health efforts. Sample parameters included (1) intake date from January 2013 through December 2015; (2) at least 18 years of age; and (3) presented at 1 of 5 primary health care clinics in Southeast Louisiana. Participants: A total of 235 patients were selected; the mean age was 44.7 years (SD = 13.6) and the majority were white (68%) and female (76%). Intervention: Brief behavioral-based trauma treatment was delivered using both on-site and telemedicine therapies provided by a psychologist, psychiatrist, or through a combined treatment model. Main Outcome Measure: The main outcome measures were the Posttraumatic Stress Civilian Checklist (PCL-C) and the Patient Health Questionnaire (PHQ-15). Results: The hypothesis was supported. Statistically significant decreases in posttraumatic stress symptoms and physical health complaints were shown over the course of treatment, with 63% of the group demonstrating clinically significant change. Conclusions: This study supports brief trauma treatment in primary care clinics as an effective method of reducing trauma and physical health symptoms in postdisaster environments.